A case study on the design, numerical modelling and preliminary testing of tension piles in weak rock. Issue 1 (August 2021) - Jackson, P; Olbekk, E; Petrella, F; Wudzka, A; Zanetti, P
Abstract: Over the last twenty years several major tunnel projects have been constructed in the Copenhagen area in the Danian limestone, either in the Copenhagen Limestone or in the Bryozoan limestone; in parallel, developments have been made in the characterization of these rocks. The Danian limestones are weak sedimentary rocks with highly variable properties in terms of their strength, stiffness and in their mass permeability. Their properties are governed by their genesis resulting in a large variation in the carbonate content, their induration and a large variability of the fissuring and distribution of fissuring. The paper describes the experience gained from selected underground construction projects in the Copenhagen area, specifically for the passive uplift anchors/tension piles that are often uses as a means to resist uplift forces resulting from the porewater pressure exerted at the underside of the base slab of major underground structures. While tension piles are common in Copenhagen, as they are often used for basement construction too, the authors are not aware of a documented calculation method. The paper presents a summary of the case histories published for ground anchors in Danian limestone and proposes a calculation method for the unit shaft resistance of small diameter tension piles as well as the comparison with numerical modelling and preliminary testing undertaken for the Sydhavn metro in Copenhagen.